An Analysis of the Primary School Teachers' Usage of Instructional Software - Kazu, Ibrahim Yasar; Yavuzalp, Nuh (Kassel Univ Press Gmbh, 2008)
This research is a descriptive study and examines instructional software usage and teacher's attitude towards instructional software. The data was gathered using mass sampling of 471 teachers from 17 primary schools in the city center of Elazig and Malatya, Turkey. Teachers signify that they can use computers for different aims as well. On the other hand, it is observed that many teachers fail to use instructional software in their lessons. In general, researches show that teachers find them favourable and useful. Moreover, teachers think that these IT classes and instructional software must be developed. Teachers think that if these instructional software are used during lessons, the concepts of lesson topics will be easier; performance of the students and their success will be positively affected.
Keywords: Computer technology; Information and communication technology; Instructional software; Primary school teachers